Wellness culture benchmarking at Preliminary School Bulgarian (Research Announcements "Heritage BG", 2025)
The School Wellness Division is regulated by legislative changes in school education, in particular the expected competencies. Key Competence No. 9 requires knowledge, skills for sustainable development, implementation of a healthy lifestyle and sports. In response to the regulations and our motivation from the participation in the project “Building and developing the Center of Excellence” Heritage BG, we are developing a dissertation for the degree of “Doctor of Science” on “Benchmarking of Wellness Culture in Bulgarian schools” in within the project. References:Dimitrova et al. 2018: Dimitrova Bistra, Mincho Polomenov, Vesela Treneva, Irina Nesheva, Vessela Ivanova, Dimitar Trendafilov. Sotsialna znachimost na uelnes (wellness) kulturata: sravnitelen analiz po danni ot nauchni izsledvania na Galap interneshanal. Monografia. Izd. Avangard, Sofia parvo izdanie, 78-92.Dimitrova et al. 2021: Dimitrova, Bistra, Nikolay Izov, Velichka Alexandrova, Rumen Iosifov, Darinka Ignatova, Dimitar Trendafilov, Vasil Petrov, Gergana Vasileva. Smart kognitiven instrumentarium. Vŭnshna otsenka na profesionalni kompetentsii za kadri v Nishov turizŭm. NSA Press: Sofia, 47-72.Kostov 2013: Kostov, Kiril. Nauchnoto izsledvane vav fizicheskoto vazpitanie, sporta i kineziterapiyata (teoretiko-prilozhni aspekti), Blagoevgrad, 27-36.Kostov et al. 2005: Kostov, Kiril, Stoyan, Ivanov, Veselin Margaritov, Boyanka Boeva. Kniga za uchitelya po fizichesko vazpitanie i sport, izd. Prosveta, Sofia.Momchilova 2011: Momchilova Antoaneta. Interaktivni metodi na obshtuvane v obuchenieto po fizichesko vazpitanie i sport – faktor za dvigatelnoto razvitie na podrastvashtite. Nauchni trudove na Rusenskia universitet, tom 50, seria 8.2., 23-29.Nikolov 2011: Nikolov, Georgi. Statistika. VUZF., Sofiya, 23-30.Popov 2003: Popov, Nikola. Lichnosti. Motivatsiya. Sport. NSA-PRES, tom 1, Sofiya.Veselinov 2021: Veselinov, Dimitar. Dialogat v obrazovanieto, Deseti mezhdunaroden esenen nauchno-obrazovatelen forum. Dialogat v obrazovanieto – suvremennost i perspektivi, 11-16.Dimitrova 2020: Dimitrova, Bistra. Relationships Between Education and Innovations in the Recreational Industry in Bulgaria. Trakia Journal of Sciences, 18 (2), 143-149.Dimitrova 2019: Dimitrova, Bistra. Quality Assessment about Standards for Wellness Services and Certified Skills of Specialized Staff. Trakia Journal of Sciences, 17 (2), 143-149.Donev et al. 2019: Donev Jordan, Stoyan Andonov, Stefka Djobova, Jordan Jordanov Donev, Oleg Hristov, Ivelina Kirilova, Stoyan Bahchevanski, Rumen Iossifov, Velichka Aleksandrova, Bogomil Angelov, Nataliq Stoyanova. Comparative study of measuring physical activity among sport students. Original scientific paper. Conference: International scientific congress ‘Applied sports sciences. Balkan scientific congress of physical education, sports and health’, 15 – 16 November 2019, Sofia, Bulgaria. Proceeding book, 369-374.Ignatova, Iliev 2020: Ignatova, Darinka & Alexandar Iliev. Motor Qualities and Their Influence on the Children’s Development. International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism, 2, (1-2), 16-44.Ivanova 2019: Ivanova Vessela. Influence of Gymnastic Exercises in the Water Environment. International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism, 1 (1), 53-56.Konchev 2019: Konchev Mihail. Big Data, Neural Network and Predictive Analytics: Application in the Field of Sport. International Scientific Congress ‘Applied Sports Sciences’ and Balkan scientific congress ‘Physical Education, Sports, Health’ in Sofia, Bulgaria, 2019, 393-397.Nesheva 2019: Nesheva Irina. Study of Results Between Initial and Final Specific Tests in Women with Normal Pregnancy. Trakia Journal of Sciences. No 17 (2), 135-142.Nesheva 2020: Nesheva Irina. InformationSystem for Inclusion of Women with Normal Pregnancy in Gymnastics Program. ‘Smart Innovations on the Recreative & Wellness Industries and Niche tourism’, Sofia, No 2 (1), 33-39.Trendafilov, Dimitrova 2013: Trendafilov, Dimitar, Bistra Dimitrova. Aqua Spinning as Anti stress Health Prevention. Sport Mont, Vol. XI (37-38-39), 467-473.
Keywords: motor potential; indicators of student mobility; functional activity; a lesson in physical education and sports